Il Secolo Illustrato, Domenica 25 Luglio 1897 - Unknown (Massachusetts Institute of Technology. Libraries. Department of Distinctive Collections, 1897)
Issue of the Italian newspaper "Il Secolo Illustrato" with a front page illustration showing S.A. Andrée's balloon sailing over a seaside town with guide rope attached. An inset illustration shows a portrait of Andrée. The accompanying article is on page 238. For more information about this item, visit https://archivesspace.mit.edu/repositories/2/digital_objects/811